Integrating African indigenous knowledge in African schools to decolonise science education - Aina, Jacob Kola (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to critically review the integration of African Indigenous Knowledge (AIK) into the science curriculum as a strategy to decolonise science education in Africa. Using a literature review method, the paper synthesises insights from 20 peer-reviewed journal articles, three edited book chapters, one bibliography, one conference proceeding, and one public lecture, published between 2018 and 2023. The findings reveal that integrating AIK into science education enhances cultural relevance, increases student engagement, and uncovers the scientific potential historically suppressed by the dominance of Western knowledge systems and language barriers. The paper proposes the Integrated Indigenous Knowledge Science Education (IIKSE) curriculum framework and emphasises the importance of teaching science in African Indigenous languages. This research implies the need for comprehensive teacher training, interdisciplinary curriculum development, and collaborative engagement with Indigenous communities. Such efforts are essential to build an inclusive, sustainable, and contextually meaningful science education system that empowers African students and promotes the recognition of local knowledge systems.